BUDIDAYA SAYURAN SISTEM HIDROPONIK DI KELURAHAN PARDOMUAN KECAMATAN SIANTAR TIMUR KOTA PEMATANGSIANTAR - Ummu Harmain; Jef Rudiantho Saragih (Universitas, 2021)
The limited land available has made the community less interested in farming. Even the small amount of household vegetable needs is obtained from markets and stalls. For this reason, the community needs to be given knowledge of vegetable farming by utilizing existing land so that at least it is able to meet the family's vegetable needs and if possible can increase household income. The output plan for this activity is: (1) Participants have technical skills in cultivating several types of vegetables; (2) Participants have technical knowledge and skills of hydroponic system vegetable cultivation; (3) Participants are able to produce several types of fresh vegetables; (4) Participants receive additional income; and (5) The local area can become a demonstration plot for similar activities. Methods and outcomes of activities: extension (100%), hydroponic vegetable cultivation practice (100%), sales (25%), and promotion activities (25%). The results and outcomes obtained in the community service activities carried out include increased public understanding of vegetable cultivation and hydroponic systems, vegetable self-sufficiency, utilization of empty space in the yard